Monitoring of Dual CRISPR/Cas9-Mediated Steroidogenic Acute Regulatory Protein Gene Deletion and Cholesterol Accumulation Using High-Resolution Fluorescence In Situ Hybridization in a Single Cell - Lee, Jinwoo; Jefcoate, Colin (Frontiers in Endocrinology, 2017)
Recent advances in fluorescence microscopy, coupled with CRISPR/Cas9 gene editing technology, provide opportunities for understanding gene regulation at the single-cell level. The application of direct imaging shown here provides an in situ side-by-side comparison of CRISPR/Cas9-edited cells and adjacent unedited cells. We apply his methodology to the StAR gene in Y-1 adrenal cells and MA-10 testis cells. StAR is a gatekeeper protein that controls the access of cholesterol from the cytoplasm to the inner mitochondria. The loss of this mitochondrial cholesterol transfer mediator rapidly increases lipid droplets in cells, as seen in StAR-/- mice. Here, we describe a dual CRISPR/Cas9 strategy marked by GFP/mCherry expression that deletes StAR activity within 12 h. We used single-molecule fluorescence in situ hybridization (sm-FISH) imaging to directly monitor the time course of gene editing in single cells. We achieved StAR gene deletion at high efficiency dual gRNA targeting to the proximal promoter and exon 2. Seventy percent of transfected cells showed a slow DNA deletion as measured by PCR, and loss of Br-cAMP stimulated transcription. This DNA deletion was seen by sm-FISH in both loci of individual cells relative to non-target Cyp11a1 and StAR exon7. sm-FISH also distinguishes two effects on stimulated StAR expression without this deletion. Br-cAMP stimulation of primary and spliced StAR RNA at the gene loci were removed within 4 h in this dual CRISPR/Cas9 strategy before any effect on cytoplasmic mRNA and protein occurred. StAR mRNA disappeared between 12 and 24 h in parallel with this deletion, while cholesterol ester droplets increased fourfold. These alternative changes match distinct StAR expression processes. This dual gRNA and sm-FISH approach to CRISPR/Cas9 editing facilitates rapid testing of editing strategies and immediate assessment of single-cell adaptation responses without the perturbation of clonal expansion procedures.